Structural breaks in the real exchange rate adjustment mechanism - Laurence Copeland; Saeed Heravi (Cardiff University, Cardiff Business School, 2006)
We show that the behaviour of the real exchange rates of the UK, Germany, France and Japan has been characterised by structural breaks which changed the adjustment mechanism. In the context of a Time-Varying Smooth Transition AutoRegressive of the kind introduced by Lundbergh et al (2003), we show that the real exchange rate process shifted in the aftermath of Black Wednesday in the case of the Pound, in 1984-5 in the case of the Franc and, more tentatively, during the Asian crisis of 1997-8 in the case of the Yen.
Keywords: 330